Analytical and Numerical Solutions for Glial Cells Interactions between Immunotherapy and Cancer Cells - Kaviyan, E. Vargees; Jayakumar, T.; Sujitha, S.; Maheskumar, D. (Communications in Mathematics and Applications, 2023)
In this article, we investigate a mathematical modeling applying a system of differential equations, that explains a interaction of healthy cells, glioma cells, macrophages, CD8+ T cells, and immunotherapy. Further, analytical method has been investigated. Moreover, the stability analysis and numerical simulations are also given for our proposed model. Finally, the quality of our model is also examined by comparing the graph of the analytical method and numerical simulation.
Keywords: Brain tumor; Immunotherapy; Glial cells; Glioma cells; Analytical solution